Precursor-Directed Generation of Indolocarbazoles with Topoisomerase IIα Inhibitory Activity - Cong Wang; Adeep Monger; Liping Wang; Peng Fu; Pawinee Piyachaturawat; Arthit Chairoungdua; Weiming Zhu (Marine Drugs, 2018)
One new indolocarbazole, 3-hydroxy-K252d (3), together with the recently reported 3-hydroxyholyrine A (1) and 3′-N-acetyl-3-hydroxyholyrine A (2), were obtained by feeding a culture of the marine-derived Streptomyces strain OUCMDZ-3118 with 5-hydroxy-l-tryptophan. Their structures were elucidated on the basis of spectroscopic analysis. Compound 1 potently induced apoptosis of gastric cancer cells by inhibiting topoisomerase IIα enzyme activity and reducing the expression of antiapoptosis protein level. Compound 3 displayed moderate cytotoxicity against the A549 and MCF-7 cell lines with IC50 values of 1.2 ± 0.05 μM, 1.6 ± 0.09 μM, respectively.